PENGARUH IPM, UPAH MINIMUM PROVINSI DAN BELANJA DAERAH TERHADAP KEMISKINAN DI KABUPATEN ACEH BARAT - Agustyn, Adelia Dara; Badli, Saiful; Ertika, Yenny; Noviar, Helmi; Ariani, Dian (EKOMBIS: JURNAL FAKULTAS EKONOMI, 2025)
This study investigates the impact of the Human Development Index (HDI), provincial minimum wage, and regional expenditure on the poverty level in West Aceh Regency during the period 2011–2023. The research adopts a quantitative approach using multiple linear regression methods and secondary data sourced from the Central Bureau of Statistics (BPS) of West Aceh. Analysis was conducted using EViews 10 software to examine both partial and simultaneous effects of the independent variables on the dependent variable, namely the number of people living in poverty. The results indicate that, partially, the HDI has a negative and significant effect on poverty (0.0154 < 0.05), implying that improvements in the HDI correlate with reductions in poverty. In contrast, the provincial minimum wage (0.3722 > 0.05) and regional expenditure (0.2691 > 0.05) both exhibit negative but statistically insignificant partial effects. This suggests that increases in wages and regional spending alone are not sufficient to significantly reduce poverty in West Aceh. This may be due to other factors, such as suboptimal budget allocation and an economy still dominated by the informal sector. However, the simultaneous analysis shows that HDI, provincial minimum wage, and regional expenditure collectively have a significant effect on poverty (0.000276 < 0.05). The coefficient of determination (R-squared) is 0.867304, indicating that 86.7% of the variation in poverty can be explained by this model, while the remaining 13.3% is due to factors outside the model. These findings underscore the importance of a holistic approach to poverty alleviation, involving the enhancement of HDI, increases in minimum wages, and the optimization of the allocation and effectiveness of regional expenditure. Future research could consider additional factors contributing to poverty in West Aceh to develop a more comprehensive model.